Antioxidant activity of aminоderivatives of santonin extracted from the plant Artemisia gracil. Krasch. - Zhumagaliyeva, Zh.Zh.; Dzhalmakhanbetova, R.I.; Eleupaeva, Sh.K.; Korchyn, V.I. (Fundamental and Experimental Biology, 2018)
In this paper, the results of a study of the biologicalactivity of amino derivatives of sesquiterpene lactone santonin are shown. The study of the antioxidant activity of santonin and their amino derivatives was carried out using the method of initiated biochemiluminescence. And also the above-ground part of the plant Artemi-sia gracil.Krasch. — wormwood finely-chained by the chloroform extraction method, the sum of extractive substances is obtained. As a result of column chromatography of the sum of extractive substances, sesquiterpenoid santonin was isolated. Synthesis of natural sesquiteroids with an amino group allows the preparation of new compounds with a wide spectrum of biological activity, as well as the formation of com-pounds that have a higher solubility in water than the original lipophilic sesquiterpenoids. Considering this, the reaction of santonine with primary amines with monoethanolamine and methylamine was studied. The structures of santonine and amino derivatives were identified using modern physicochemical methods and IR and PMR spectra. 13C NMR spectra were recorded on Bruker AC 200 spectrometers [operating frequencies 200]. Keyw